TRANSFORMASI DIGITAL DALAM MANAJEMEN KURIKULUM: ANALISIS IMPLEMENTASI BLENDED LEARNING DI SEKOLAH ISLAM - Muchlis Anshori (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2025)
Digital transformation has significantly reshaped education systems, including curriculum management in Islamic schools. Blended learning has emerged as a strategic approach that integrates online and face-to-face learning to enhance flexibility and effectiveness. However, its implementation still faces challenges, particularly in curriculum integration and the incorporation of Islamic values. This study aims to analyze the implementation of blended learning in curriculum management within Islamic schools, identify key success factors, and propose a conceptual model adaptable to digital transformation. This research employs a qualitative approach using a systematic literature review, drawing on recent academic journals, scholarly books, and policy reports. Data analysis was conducted through data reduction, categorization, interpretation, and synthesis. The findings reveal that blended learning implementation remains at an adaptive stage with varying levels of integration. Its success is influenced by teachers’ digital competence, technological infrastructure, policy support, and student readiness. Furthermore, blended learning contributes to curriculum flexibility but has not yet fully driven structural transformation. Therefore, an integrative curriculum management model that combines technology, pedagogy, and Islamic values is essential.